Kvalifikator ekspr. v Slovarju slovenskega knjižnega jezika na ravni frazeologije - Logar Berginc, Nataša (Jezik in slovstvo, 2001)
The paper aims at determining the criteria underlying the use of qualifier ekspr. (=expressive) with a majority of phrasemes in the Dictionay of the Slovene Standard LIterary Language. Constituents of phrasemes, their use, position of a phraseme within a dictionary entry and material itself were examined. The findings imply that in marking phrasemes as expr. the dictionary's authors mainly guised by their language instinct.
Keywords: Slovene; slovenščina; frazeologija; phraseology; Slovar slovenskega knjižnega jezika